Exploring Strategies to Enhance the Presentation of Information in Print DTCA to Improve Consumers' Recall of Information - Monica J Hwang; Shih-Ying Hsu (University of Minnesota Libraries Publishing, 2017)
This study examines how best to present information in an antidepressant print DTCA. The objectives of this study are to: (1) modify an antidepressant print advertisement to enhance consumers' understanding of the presented information, (2) create a questionnaire to measure consumers' recall of the information presented in an antidepressant print advertisement and (3) pilot test the study instruments by comparing consumers' recall of the information in the antidepressant print advertisement between those who view the original advertisement and those who view the modified advertisement. Modifications of the advertisement were based on the Explanatory Structure Building Model, findings from previous studies, and literature pertaining to the enhancement of the readability and comprehension of written health information. Data collection was conducted in three stages using mixed methods. This study details potential techniques that can be used to enhance the presentation of information in print DTCA in order to improve consumers' recall of the information. Furthermore, this study shows that strategies to improve the presentation of information in print DTCA exist and that the strategies are feasible to apply. Conflict of Interest This research study was supported by the University of Wisconsin-Madison Population Health Dissertation Grants sponsored by the Robert Wood Johnson Foundation and the Sonderegger Research Center Dissertation Research Grants.   Type: Original Research